1995
DOI: 10.1038/nm0295-154
|View full text |Cite
|
Sign up to set email alerts
|

Non-steroidal anti-inflammatory drugs (NSAIDs) associate with zwitterionic phospholipids: Insight into the mechanism and reversal of NSAID-induced gastrointestinal injury

Abstract: The molecular basis of the injurious actions of non-steroidal anti-inflammatory drugs (NSAIDs) on the gastrointestinal (GI) tract is only partly understood. In this study we have obtained evidence, employing both in vitro and in vivo systems, that five NSAIDs have the ability to form a chemical association with zwitterionic phospholipids. Since this same class of phospholipids line the luminal aspects of the mucus gel layer to provide it with non-wettable properties, this intermolecular association may be the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
194
0
4

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 287 publications
(201 citation statements)
references
References 18 publications
3
194
0
4
Order By: Relevance
“…Ibuprofen and other NSAIDs have been found to spontaneously associate with zwitterionic phospholipids such as PC due to both electrostatic and hydrophobic interactions (17,18). Accordingly we investigated whether pre-association of ibuprofen and purified soy PC (90G) had an influence on COX activity that differed from the inhibitory effect when the same concentrations of ibuprofen and PC were added separately.…”
Section: Effects Of Premixing Ibuprofen With Phospholipid On Inhibitomentioning
confidence: 99%
See 1 more Smart Citation
“…Ibuprofen and other NSAIDs have been found to spontaneously associate with zwitterionic phospholipids such as PC due to both electrostatic and hydrophobic interactions (17,18). Accordingly we investigated whether pre-association of ibuprofen and purified soy PC (90G) had an influence on COX activity that differed from the inhibitory effect when the same concentrations of ibuprofen and PC were added separately.…”
Section: Effects Of Premixing Ibuprofen With Phospholipid On Inhibitomentioning
confidence: 99%
“…In humans, pre-associating PC with aspirin or other NSAIDs produced less gastric damage than aspirin alone, without decreasing the COX inhibition (17,18,33), and formulations of NSAID with PC are being considered as one approach to lowering gastrointestinal side effects of these agents (34). The protective action of PC in this setting has been attributed to actions at the surface of gastric mucosal cells that is distinct from COX inhibition (35).…”
Section: In Vivo Implications Of Cox Inhibitor Potentiation By Pcmentioning
confidence: 99%
“…The diffusion of salicylates from the aqueous phase to the oil phase was monitored by pipetting samples from the cyclohexane phase after 1 h. The presence of salicylates in the organic phase was assessed¯uorometrically (excitation 280 nm, emission 310 nm). 13 …”
Section: Diffusion Studiesmentioning
confidence: 99%
“…This work led to reports by our lab and those of other investigators that NSAIDs can induce surface injury to the GI mucosa by chemically associating with PC present in mucus and cell membranes [30,31], thereby compromising these important barriers. These findings ultimately led to the development of a family of soy-derived PC-NSAIDs that have been demonstrated to have reduced GI toxicity in rodents [30] and in a number of clinical endoscopic trials, while fully maintaining the therapeutic activity of the NSAIDs [32,33].…”
mentioning
confidence: 86%
“…Revisiting the Sippy diet approach, our lab demonstrated the importance of phospholipids in milk in ulcer protection and healing (overriding the effects of increased gastric acid secretion) [29], and also demonstrated that synthetic and soy lecithin-derived (PC) could protect against damaging agents or conditions (e.g., stress) [10]. This work led to reports by our lab and those of other investigators that NSAIDs can induce surface injury to the GI mucosa by chemically associating with PC present in mucus and cell membranes [30,31], thereby compromising these important barriers. These findings ultimately led to the development of a family of soy-derived PC-NSAIDs that have been demonstrated to have reduced GI toxicity in rodents [30] and in a number of clinical endoscopic trials, while fully maintaining the therapeutic activity of the NSAIDs [32,33].…”
mentioning
confidence: 97%